An introduction to electronic materials for engineers - Gao, Wei; Li, Zhengwei 1970-; Sammes, Nigel M. (World Scientific, 2011)
"An Introduction to Electronic Materials for Engineers aims to give a basic understanding and comprehensive overview of a wide range of materials, such as conducting materials, semiconductors, magnetic materials, optical materials, dielectric materials, superconductors, thermoelectric materials and ionic materials. The new chapters added into this latest edition include thin film electronic materials, organic electronic materials and nanostructured materials. These chapters aim to reflect the new developments made in electronic materials and nanotechnology research towards the design and fabrication of modern equipment and electronic devices. This book is designed for undergraduate engineering and technology students who have background knowledge of physics and chemistry, as well as for engineers who work on materials processing or application, or electric/electronic engineering. It emphasizes on the synthesis, performance and application of electronic materials and will enable readers to understand and relate to the devices and materials."